1989
DOI: 10.1111/j.1751-1097.1989.tb04178.x
|View full text |Cite
|
Sign up to set email alerts
|

PHOTO‐INDUCED ELECTRON EJECTION FROM THE REDUCED COPPER OF Pseudomonas aeruginosa AZURIN

Abstract: The reduced form of Pseudomonas aeruginosa azurin exhibits an enhanced absorbance in the UV compared to that of the oxidized protein. This enhancement has also been observed for azurins from other bacterial species and for another type I copper protein, plastocyanin. Pulsed laser excitation of the reduced azurin in the region of enhanced absorbance at 308 nm results in single photon, rapid (less than 30 ns) oxidation of the copper center and formation of the hydrated electron with a quantum yield of 0.05. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…The observed redox chemistry of the Cu center can be attributed to several mechanisms that may be occurring in solution, and shown in Figure 5: path A, ET from Cu I to photogenerated W48• + ; path C, direct electron ejection 60 from Cu I to generate Cu II ; and path D, ET from Cu I to photogenerated W48*. 55 Protein degradation is also possible.…”
Section: ■ Discussionmentioning
confidence: 99%
“…The observed redox chemistry of the Cu center can be attributed to several mechanisms that may be occurring in solution, and shown in Figure 5: path A, ET from Cu I to photogenerated W48• + ; path C, direct electron ejection 60 from Cu I to generate Cu II ; and path D, ET from Cu I to photogenerated W48*. 55 Protein degradation is also possible.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Experimentally, electron-transfer processes can be examined by adding exogenous oxidants and reductants or by using photons to try to induce electron transfer. 4,11 For azurin numerous studies have concentrated on Trp-48 because it may be involved in electron trnasfer to the Cu site.3,5,7 Many of the unique absorption and fluorescence spectral features of Pae azurin (as well as Pseudomonas fluorescens ATCC-13525-2 (Pfl) azurin5,7) can be attributed to this single Trp residue. 3,5,[12][13][14][15] Several groups have investigated the Trp fluorescence behavior in azurins from different bacterial strains with the expectation of characterizing the Trp environment and interactions between the Trp and potential redox partners involved in the electrontransfer conduit.…”
Section: Introductionmentioning
confidence: 99%
“…When Corren et al (1987) observed the NO binding to Az, they suggested that it formed a charge transfer complex, Cu+-NO+, partly based on their observation of bleaching of the main absorption bands, which is also observed in reduction of the copper. However, the azurin spectra in Figure la show an isosbestic point at ~530 nm and increasing absorbance below that wavelength, indicating that a band appears around 400 nm, which does not exist in reduced Az (Corin & Gould, 1989). Halocyanin shows the same behavior, as evident from the spectra in Figure lb,c.…”
Section: Discussionmentioning
confidence: 55%